2006
DOI: 10.1111/j.1467-8535.2006.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaming in a 3D multiuser virtual environment: engaging students in Science lessons

Abstract: Based on the exploratory study of a 3D multiuser virtual environment (3D MUVE), known as Quest Atlantis (QA), in a series of Primary Four (10-to 11-year-olds) Science lessons at Orchard Primary School in Singapore, this paper examines the issues of learning engagement and describes the socio-cultural context of QA's implementation. The students and teacher were observed during the lessons, interviewed after, and the completed quests were analysed to determine the level of engagement achieved. A pre-and posttes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(106 citation statements)
references
References 18 publications
6
64
0
12
Order By: Relevance
“…Lim, Nonis and Hedberg (2006) observed that students are more motivated when allowed to use multi-user cyber games during their lessons. Abrams' (2008) study showed that the motivation test statistically supports playing computer games to increase student motivation as well as increasing their interest in math.…”
Section: Discussionmentioning
confidence: 99%
“…Lim, Nonis and Hedberg (2006) observed that students are more motivated when allowed to use multi-user cyber games during their lessons. Abrams' (2008) study showed that the motivation test statistically supports playing computer games to increase student motivation as well as increasing their interest in math.…”
Section: Discussionmentioning
confidence: 99%
“…It builds on earlier research studies on the implementation of QA in the United States (Barab, Thomas, Dodge, Carteaux & Tuzun, 2005) and Singapore (Lim, Nonis & Hedberg, 2006). The main outcome of these works is the building of a socially responsive online environment and context that is academically valuable, game like, and engaging to students of both genders.…”
Section: Background To the Researchmentioning
confidence: 99%
“…The basic philosophy of inquiry based learning is to make learning more meaningful, more transferable to various situations out of a specific context, and more conducive to self directed lifelong learning (Lim, Nonis & Hedberg, 2006). NWREL (1997) suggests that in practice, inquiry often occurs on a continuum.…”
Section: Inquiry Based Learning and Quest Atlantismentioning
confidence: 99%
“…For example, Lim et al (2006) question the assumption that students' engagement in computer game play necessarily leads to engagement in the learning task embedded in the setting. In their study, they found that the computer game Quest Atlantis succeeded to serve as an intrinsic motivation factor, but that some students were so immersed in the game world that they lost focus on their school assignment.…”
Section: Computer Game Play In Educational Settings As a Motivationalmentioning
confidence: 99%